The Relevance and Importance of Criminological Research on the Problems of the Legal Fight against Latent Crime in Kazakhstan - ABDRAMANOVA, Nazira K.; ALAUKHANOV, Yesbergen O.; ALIMBEKOVA, Madina A.; MAULENOV, Duman B.; AYANBAYEV, Yeldar S. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).01, 2019)
Today it is very difficult to get real and reliable indicators of the state of all crime. Since we do not have accurate data of latent crime, which is undoubtedly part of the whole crime. The purpose of this scientific work is the criminological assessment of latent crime and existing problems in combating it, by conducting a criminological analysis of statistical crime indicators for the period from 2010 to 2018, according to officially submitted data of the Committee of Legal Statistics and Special Records of the General Prosecutor's Office of Kazakhstan, which will reveal the whole essence of the latency of crime in the country. According to the results of the study, the authors come to the conclusion about the safe existence of hidden crime in Kazakhstan, and the need to study all the factors and causes that contribute to its existence, development and growth. This proves the relevance of the study of this issue and its great importance in the further successful struggle both with the latency of crime and with all common crime.